The Role of Correctional Institution Officers in the Process of Fostering Prisoners in Order to the Realization of the Correctional System (Study in Correctional Institution Class II-A Pancur Batu) - Heri Novetinus Sitepu; T. Riza Zarzani; Syaiful Asmi Hasibuan (ASIAN PUBLISHER, 2024)
This research was conducted with the aim of knowing the role of Correctional Institution Officers in the Process of Guiding Prisoners for the Realization of the Correctional System (Study at Class II-A Pancur Batu Correctional Institution) and to find out the obstacles faced by correctional officers and solutions that have been carried out by correctional officers in coaching prisoners for the realization of the correctional system. The method used in this research is juridical sociological to get real legal research by going directly to the object, primary data obtained directly from the source through interviews with correctional officers and prisoners concerned, and secondary data used as supporting data in this study. From the results of the research obtained, the role of Class II-A Pancur Batu Correctional Institution Officers in the implementation of coaching is divided into 5, namely Development of Religious Awareness, Development of awareness of nation and state, Intellectual Development, Development of Legal Awareness, Development of Integration with Society. Serious inhibiting factors for the Class IIA Pancur Batu Penitentiary are the lack of quantity of employees, the existence of inadequate facilities and infrastructure, excess capacity of prisoners and detainees, lack of coaching time.